(untitled) (Global Journal of Human-Social Science, 2014)
The globalisation trends of society have taken centre stage meaning that people around the world are required to develop high level but low cost technologies and innovative competencies in order to enhance social development. In the field of higher education, university managers need to join the technological revolution by adopting low cost ICT and Elearning facilities. This paper examines the role of E-learning in university effectiveness. With the impact of globalisation, universities have become competitive in terms of providing quality and flexible educational services. Creating an enduring vision and a strategic implementation framework to implement technological innovations and E-learning seems critical. The demand for skilled workforce, with technological to cope with the ever-changing responsibilities at the work place, warrants universities to adjust their teaching strategies beyond face-to face instruction in class.